COMPREHENSIVE REVIEW OF PERIOPERATIVE INFECTION CONTROL MEASURES FOR OPERATING ROOM TECHNICIANS. - Wabran Ali Salem Al Khuraim, Hossiun Mohammad Hamad Al Salah, Hamad Saleh Hamad Alduways, Bashayr salem al matlaq,, Ibrahim Miqradh Abdallah Al Atmi, Nwayer Masoud Sanqour Al Saad, Abdullah Mohammed Salem Alhamami, Abdulkarim Salem Alsaad, (Chelonian Research Foundation, 2023)
Before the surgery, infection control is also critical to keeping the patient safe from health-related infections. It is the function of the OR technicians to take critical actions in carrying out the infection control protocols during surgical interventions. This outline follows an exhaustive literature review regarding perioperative infection control measures for OR technicians. The review will underscore the significance of adherence to protocols and implementing strategies for minimizing contamination in addition to PPE use. Disinfection and sterilization approaches for the instruments, surfaces, and tools are also discussed in the chapter. The review summarizes primary outcomes, provides the related figures, tables, and graphs, and formulates suggestions for improving infection control procedures. Keywords: Perioperative infection control, Operating room technicians, Personal protective equipment, Sterilization, Disinfection, Healthcare-associated infections.